Analysis of Clinical Outcomes Based on Demographic Characteristics of Patients with Type 2 Diabetes Mellitus - Apriliany, Fitri; Cholisah, Elis; Zainal, Zainol Akbar; Umboro, Recta Olivia (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Diabetes is one of the top 10 causes of death worldwide. Many factors increase the risk of mortality and morbidity in patients with diabetes such as age, sex, BMI, educational attainment, and marital status.Objectives: The study aimed to analyze clinical outcomes based on patient demographics.Methods: This method was cross-sectional and was conducted at Antapani Medika Clinic, Bandung. Inclusion criteria for this study were diabetic patients who had complete medical records, and who were receiving oral antidiabetic therapy for at least 6 months. Exclusion criteria for study were patients with diabetes who were on insulin therapy, patients with tuberculosis, and pregnant and lactating women. Data on demographic characteristics were analyzed descriptively. Chi-square and likelihood ratio tests were used to analyze differences in clinical outcomes based on therapy achievement on patient demographics.Results: The results showed that HbA1c target levels were achieved by patients who were 65 years of age or older (68%), had a BMI in non-obese category (80.8%), had diabetes for six years or more (80.8%), were married (62.9%), attended college (68.4%), exercised 3 to 6 times per week (64.9%), did not smoke (61.9%), and had no comorbidities (65.3%). This study concludes that there is an association between BMI and duration of diabetes and achievement HbA1c target (p<0.05).Conclusion: The clinical implications of this study are as a guide for health workers in Indonesia in management of diabetes so that they can provide services to patients according to the medical needs of patients.